Paget´s disease of the male breast: An unusual case in a young man and literature review - Rodríguez-Fernández, Vanesa; Cameselle-Cortizo, Lucía; Lamas González, María José; De Castro Parga, Gonzalo José; Valdés-Pons, Javier; Novo Domínguez, Alejandro; Cameselle-Teijeiro, Jorge F; Schmitt, Fernando Carlos (Current problems in cancer. Case reports, 2020)
•Paget's disease of the breast is rare, comprising about 1–4% of all breast cancers. Male breast cancer is also uncommon, representing less than 1% of all breast cancer. Thus, male mammary Paget´s disease is extremely rare.•We present a postoperative diagnosis of an exceptional case of mammary Paget´s disease in man who complained of bilateral gynecomastia and mild eczematous changes in the nipple. Our case describes the youngest man diagnosed with Paget´s disease in the literature.•The detailed presentation of this case and the literature review allow us to achieve a high degree of suspicion of Paget´s disease. Clinical recognition of this entity allows an early diagnosis with a favorable prognosis. Mammary Paget's disease (PD) is characterized by eczematous changes of the nipple-areolar complex and is usually associated with an underlying breast cancer (BC). PD of the breast is rare, comprising about 1–4% of all BC. Male BC is also uncommon, representing less than 1% of all BC. Thus, male mammary PD is extremely rare. We report the case of mammary PD associated with an underlying BC in situ in a 41-year-old young man who complained of bilateral gynecomastia and mild eczematous signs in the nipple. [Display omitted]